If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying In(3x + -2) + in(x + -1) = 2inx Reorder the terms: nI(-2 + 3x) + in(x + -1) = 2inx (-2 * nI + 3x * nI) + in(x + -1) = 2inx (-2nI + 3nxI) + in(x + -1) = 2inx Reorder the terms: -2nI + 3nxI + in(-1 + x) = 2inx -2nI + 3nxI + (-1 * in + x * in) = 2inx -2nI + 3nxI + (-1in + inx) = 2inx Reorder the terms: -1in + inx + -2nI + 3nxI = 2inx Solving -1in + inx + -2nI + 3nxI = 2inx Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '-2inx' to each side of the equation. -1in + inx + -2nI + -2inx + 3nxI = 2inx + -2inx Reorder the terms: -1in + inx + -2inx + -2nI + 3nxI = 2inx + -2inx Combine like terms: inx + -2inx = -1inx -1in + -1inx + -2nI + 3nxI = 2inx + -2inx Combine like terms: 2inx + -2inx = 0 -1in + -1inx + -2nI + 3nxI = 0 Add '2nI' to each side of the equation. -1in + -1inx + -2nI + 2nI + 3nxI = 0 + 2nI Combine like terms: -2nI + 2nI = 0 -1in + -1inx + 0 + 3nxI = 0 + 2nI -1in + -1inx + 3nxI = 0 + 2nI Remove the zero: -1in + -1inx + 3nxI = 2nI Add '-3nxI' to each side of the equation. -1in + -1inx + 3nxI + -3nxI = 2nI + -3nxI Combine like terms: 3nxI + -3nxI = 0 -1in + -1inx + 0 = 2nI + -3nxI -1in + -1inx = 2nI + -3nxI Reorder the terms: -1in + -1inx + -2nI + 3nxI = 2nI + -2nI + -3nxI + 3nxI Combine like terms: 2nI + -2nI = 0 -1in + -1inx + -2nI + 3nxI = 0 + -3nxI + 3nxI -1in + -1inx + -2nI + 3nxI = -3nxI + 3nxI Combine like terms: -3nxI + 3nxI = 0 -1in + -1inx + -2nI + 3nxI = 0 Factor out the Greatest Common Factor (GCF), 'n'. n(-1i + -1ix + -2I + 3xI) = 0Subproblem 1
Set the factor 'n' equal to zero and attempt to solve: Simplifying n = 0 Solving n = 0 Move all terms containing i to the left, all other terms to the right. Add '-1n' to each side of the equation. n + -1n = 0 + -1n Remove the zero: 0 = -1n Simplifying 0 = -1n The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(-1i + -1ix + -2I + 3xI)' equal to zero and attempt to solve: Simplifying -1i + -1ix + -2I + 3xI = 0 Reorder the terms: -2I + -1i + -1ix + 3xI = 0 Solving -2I + -1i + -1ix + 3xI = 0 Move all terms containing i to the left, all other terms to the right. Add '2I' to each side of the equation. -2I + -1i + -1ix + 2I + 3xI = 0 + 2I Reorder the terms: -2I + 2I + -1i + -1ix + 3xI = 0 + 2I Combine like terms: -2I + 2I = 0 0 + -1i + -1ix + 3xI = 0 + 2I -1i + -1ix + 3xI = 0 + 2I Remove the zero: -1i + -1ix + 3xI = 2I Add '-3xI' to each side of the equation. -1i + -1ix + 3xI + -3xI = 2I + -3xI Combine like terms: 3xI + -3xI = 0 -1i + -1ix + 0 = 2I + -3xI -1i + -1ix = 2I + -3xI The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| -2(2x-3)=32 | | 3u-14=40 | | -32=-35-5n^2 | | 6=2v-16 | | 5x-2=7(2x-8) | | 2y-15=19 | | 7n^2-11n=-4 | | 9+16-9(1)2= | | r^2-4r-15=-3 | | x/9=1/6 | | 3lnx-lny=0 | | (Y-18)/6=0.7 | | -3(-5-b)=.33(b+13) | | (Y-18)/6 | | 12+8k=84 | | Y-18/6 | | 0.6(t+36)=-3(4-t) | | 19x+(-9)=-29+14x | | 12b+12b=3 | | 5/8x40 | | 9-w=215 | | 1/3.(180-×) | | 3y-15=33 | | (7-7x^2)/7 | | 12x+42=10x+50 | | 17x-1=135 | | X^2-20-3x-20=0 | | 12x-6+6=36 | | 1/-76=1/x | | -2x+8=4(x+8) | | 7=(-3)+x | | 12x+42=10x+56 |